Westward expansion : an interactive history adventure - Lassieur, Allison (You choose books, 2008)
Describes the people and events of the age of Manifest Destiny and the American West, revealing historical details from the perspective of a traveler on the Oregon Trail, a laborer, and a Sioux warrior.